Minimization of energy in scrap based electric are furnace (EAF) steel making through the use of premelter (2011)
An energy minimization route in an all scrap based EAF steel production process is presented in this paper. The attractiveness in flexibility of operation of mini-mills has driven its use by private investors in Nigeria on the upward trend. The situation is not likely to change much as the market demand for steel is not met. However, energy utilization is a major consideration in EAF steel making process route. amajor energy reduction route and productivity boosted by the use of fossil energy in the burners that are firmly installed in the furnace sidewall panels to the EAFs. Thus, primary energy fuel(gas) can be used for heating and pre- melting before the molten steel is transferred to the EAF for superheating resulting in a minimal use of high cost electricity. A shorter tap- to- tap time is envisaged through spatially separated vessels for heating and super heating of the steel.